The Implementation of Communicative Language Teaching in Teaching Reading Comprehension in Libyan Preparatory Schools - Zenb Abubakr Ibrahim
Communicative language teaching has been widely investigated and studied in the field of English language teaching. This study investigated teachers' views on the implementation of communicative language teaching in teaching reading comprehension among teachers in preparatory schools in Tarhuna. The study sought to investigate teachers' understanding of CLT features and its implementation to teach reading comprehension. This study also investigated the different teachers' teaching experience on the major difficulties on the implementation of CLT to teach reading comprehension. A mixed methodology triangulation research design was employed where data were collected using survey, observation and later interview. The questionnaires were administered to 230 teachers in the preparatory schools in Tarhuna. Ten teachers were observed in their classrooms and interviewed. The findings of the survey showed English teachers' views and perceptions were generally positive towards the implementation of CLT in the teaching of reading comprehension. Teachers' positive views towards CLT features revealed that they understand the basic features of CLT. Also, teachers agree that they face similar difficulties (past studies) in the implementation of CLT to teach reading. Teachers revealed that they understand that teachers, students, curriculum, educational system, CLT and socio- cultural contexts were identified as responsible for limiting the success of the teachers' attempts to implement this approach. The finding also indicated that teachers did not fulfil all CLT activities in teaching reading comprehension. The traditional education and beliefs by the efficiency of the principal role of the teachers made it difficult to teachers and students to accept and successfully implement CLT. The current study concluded that Libyan teachers have a knowledge by the efficiency of CLT in teaching reading but they provided limited practices. Besides that, the findings revealed that the effect of teachers' experience is significant towards CLT difficulties, students and curriculum difficulties. This study is significant because it adds to the literature new insights about EFL teachers' views and practices of the CLT in teaching reading comprehension as western educational structural in non- western sitting. Also, it provides invaluable information to the teachers' implementation process of CLT and invaluable facts that can be used for the revision and improvement to the teachers' way of teaching reading comprehension.